2012
DOI: 10.1177/1098300712437042
|View full text |Cite
|
Sign up to set email alerts
|

Improving Social Engagement and Initiations Between Children With Autism Spectrum Disorder and Their Peers in Inclusive Settings

Abstract: Children with Asperger’s Disorder often have difficulty with peer relationships and socialization. The current study assessed whether peer social interactions would improve in school settings if an intervention was designed that incorporated the children with Asperger’s interests. Three children who were fully-included in regular education classes but did not interact with peers prior to intervention participated in this research. Social lunch clubs, open to both the study participants and their typical peers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(99 citation statements)
references
References 32 publications
5
87
0
6
Order By: Relevance
“…In one study, participants were provided a choice of preferred or less preferred items during play (Boyd et al 2007), and in the second, preferred interests were identified and served as the theme for a social club (Koegel et al 2012). Both used a pre-assessment process to determine the preferences of children with ASD (Boyd et al 2007;Koegel et al 2012).…”
Section: Collateral Skill Interventionsmentioning
confidence: 99%
“…In one study, participants were provided a choice of preferred or less preferred items during play (Boyd et al 2007), and in the second, preferred interests were identified and served as the theme for a social club (Koegel et al 2012). Both used a pre-assessment process to determine the preferences of children with ASD (Boyd et al 2007;Koegel et al 2012).…”
Section: Collateral Skill Interventionsmentioning
confidence: 99%
“…Efficacy has been measured through a variety of means and most commonly through parent report measures (e.g., Gabriels et al 2012;Shin et al 2011;Valenti et al 2010). Very few studies reported the use of rigorous measurement techniques such as blinded clinician ratings or objectively coded naturalistic behavioral observations (e.g., Koegel et al 2012;McMahon et al 2013). As the initial efficacy results indicate the usefulness of social skills groups for adolescents with ASD, these more advanced measurements of change are suggested for use in the next wave of intervention studies.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, a intervenção foi considerada apropriada e viável para ser desenvolvida em ambientes naturalísticos, como escolas, onde o controle sobre as variáveis é menor. Na mesma linha de investigação, Koegel et al (2012) avaliaram se a socialização melhoraria os interesses de interação das crianças com autismo quando mediadas por seus pares. O estudo utilizou um delineamento experimental com linha de base múltipla, em que participaram três crianças com autismo,com média de idade entre quatro e cinco anos, matriculados na pré-escola.…”
Section: Origens Tipos E Implicações Da Impunclassified
“…A utilização de pares como forma de intervenção na sala de aula mostra resultados positivos não somente para a o aluno com autismo, mas também para seus colegas Koegel, Vernon, Koegel, Koegel & Paullin, 2012). Há evidências de que os colegas que participaram das intervenções também aumentaram seu conhecimento sobre autismo e incrementaram atitudes positivas para com colegas com deficiência (Kasari et al, 2012;Mason et al, 2014;Thiemann & Goldstein, 2004).…”
Section: Introdução: Definições E Pressupostos Da Impunclassified